DISTRIBUTION AND GEOINFORMATION DATA OF TRIPLOPHYSA STRAUCHII (KESSLER, 1874) IN WATER BASINS OF FERGANA VALLEY (Scientific journal of the Fergana State University, 2024)
Geographic information systems (GIS) of fish allows for accurate estimation of their distribution and population density. Endemic species in need of protection, as well as invasive fish species accidentally introduced from one water body to another, will provide important parametric results, such as fluctuations in population dynamics, distribution of species depending on how clean or dirty water bodies. Our research is devoted to invasive fish, and this article talks about the spotted thicklip loach (Triplophysa strauchii (Kessler, 1874)), which accidentally entered the water bodies of our region, and the extent of distribution of the species is given based on geographic information systems of fish data.